Flux composition, solder composition, and electronic board

JP7633975B2Active Publication Date: 2025-02-20TAMURA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022151774
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-22
Publication Date
2025-02-20
Estimated Expiration
2042-09-22

AI Technical Summary

Benefits of technology

【0006】 本発明の一態様によれば、ボイドの発生を十分に抑制でき、かつ部品下のはんだボールの発生を十分に抑制できるフラックス組成物、はんだ組成物、並びに、電子基板を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633975000001
    Figure 0007633975000001
Patent Text Reader

Abstract

To provide a flux composition capable of effectively preventing the occurrence of voids and also significantly reducing the formation of solder balls under components.SOLUTION: A flux composition comprises (A) a resin, (B) an activator, and (C) a hydroxy group-containing compound with a hydroxy group. The component (A) comprises (A1) a rosin-based resin with a softening point of 100°C or lower. The component (B) comprises (B1) a C3-5 dicarboxylic acid. The component (C) comprises (C1) a hydroxy group-containing compound with a residual rate of 40 mass% or more at 240°C in thermogravimetry. The content of the (A1) component is 32 mass% or more relative to 100 mass% of the flux composition. The content of the (C1) component is 10 mass% or more relative to 100 mass% of the flux composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flux composition, a solder composition, and an electronic board. [Background technology]

[0002] The solder composition is a mixture of solder powder and a flux composition (rosin resin, activator, solvent, etc.) kneaded into a paste (see Patent Document 1). This solder composition is required to have solderability, void suppression, printability, etc. On the other hand, the trend in semiconductor packages is to require high-density mounting by making components smaller and lower-profile, or high electrical characteristics, in order to achieve higher functionality. To meet this demand for higher functionality, a stable supply of power from the power source is now necessary, and so the mounting of inductor components is on the rise. This has resulted in a need to mount not only conventional chip capacitors, but also mixed inductor components with electrodes on the bottom surface. When mounting multiple components together, electrode voids in inductor components and solder balls under the components are issues. These two characteristics are mutually exclusive, and improving one characteristic deteriorates the other. Therefore, there was a demand for a material or method that could satisfy both characteristics and improve these issues. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5887330 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a flux composition, a solder composition, and an electronic board that can sufficiently suppress the occurrence of voids and the occurrence of solder balls under components. [Means for solving the problem]

[0005] According to the present invention, there are provided a flux composition, a solder composition, and an electronic board as described below. [1] A flux composition comprising: (A) a resin; (B) an activator; and (C) a hydroxyl-containing compound having a hydroxyl group, The component (A) contains (A1) a rosin-based resin having a softening point of 100° C. or lower, The component (B) contains (B1) a dicarboxylic acid having 3 to 5 carbon atoms, The component (C) contains (C1) a hydroxyl group-containing compound having a residual rate of 40% by mass or more at 240°C in thermogravimetry, The blending amount of the (A1) component is 32% by mass or more relative to 100% by mass of the flux composition, The blending amount of the (C1) component is 10 mass% or more with respect to 100 mass% of the flux composition. Flux composition. [2] The flux composition according to [1], The component (C1) is at least one selected from the group consisting of isobornylcyclohexanol and polyoxyalkylene glycol. Flux composition. [3] The flux composition according to [1] or [2], Further, (D) a thixotropic agent is contained, Flux composition. [4] A flux composition according to any one of [1] to [3] and (E) a solder powder. Solder composition. [5] A soldered portion using the solder composition according to [4] is provided. Electronic board. Effect of the Invention

[0006] According to one aspect of the present invention, it is possible to provide a flux composition, a solder composition, and an electronic substrate that can sufficiently suppress the occurrence of voids and the occurrence of solder balls under components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] [Flux composition] First, the flux composition according to the present embodiment will be described. The flux composition according to the present embodiment is a component other than the solder powder in the solder composition, and contains (A) a resin, (B) an activator, and (C) a hydroxyl-containing compound having a hydroxyl group, which will be described below. The (A) component contains (A1) a rosin-based resin having a softening point of 100°C or less, the (B) component contains (B1) a dicarboxylic acid having 3 to 5 carbon atoms, and the (C) component contains (C1) a hydroxyl-containing compound having a residual rate of 40% by mass or more at 240°C in thermogravimetry. The blending amount of the (A1) component is 32% by mass or more relative to 100% by mass of the flux composition, and the blending amount of the (C1) component is 10% by mass or more relative to 100% by mass of the flux composition.

[0008] The reason why the flux composition according to the present embodiment can sufficiently suppress the occurrence of voids and also sufficiently suppress the occurrence of solder balls under components is not necessarily clear, but the inventors speculate as follows. That is, the inventors first surmised that the solder balls under the components are caused by heat dripping that occurs when the temperature is raised from room temperature to about 200°C (low temperature range). In the present invention, the dicarboxylic acid (B1) having 3 to 5 carbon atoms improves the solder cohesive strength, thereby suppressing heat dripping in the low temperature range. Therefore, the occurrence of solder balls under the components can be sufficiently suppressed. The inventors also speculated that the voids are due to a decrease in the fluidity of the flux at temperatures of about 200°C to 250°C (high temperature range). In the present invention, a predetermined amount or more of (A1) rosin-based resin having a softening point of 100°C or less, which is a component that does not solidify easily, is used as the resin (A). Furthermore, in the present invention, the fluidity of the flux can be ensured in a high temperature range by using a predetermined amount or more of (C1) a hydroxyl-containing compound having a residual rate of 40 mass% or more at 240°C in thermogravimetry. Therefore, the occurrence of voids can be sufficiently suppressed. The present inventors presume that the effects of the present invention are achieved in the above manner.

[0009] [Component (A)] Examples of the (A) resin used in this embodiment include rosin resin, acrylic resin, epoxy resin, and phenol resin. These may be used alone or in combination of two or more. Among these, rosin resin or acrylic resin is preferred from the viewpoint of viscosity stability. Examples of the rosin-based resin include rosins and rosin-based modified resins. Examples of the rosins include gum rosin, wood rosin, and tall oil rosin. Examples of the rosin-based modified resin include disproportionated rosin, polymerized rosin, hydrogenated rosin, and derivatives thereof. Examples of the hydrogenated rosin include fully hydrogenated rosin, partially hydrogenated rosin, and hydrogenated products of unsaturated organic acid-modified rosins (also called "hydrogenated acid-modified rosin"), which are modified rosins of unsaturated organic acids (aliphatic unsaturated monobasic acids such as (meth)acrylic acid, aliphatic unsaturated dibasic acids such as α,β-unsaturated carboxylic acids such as fumaric acid and maleic acid, unsaturated carboxylic acids having aromatic rings such as cinnamic acid, etc.). These rosin-based resins may be used alone or in combination of two or more. Among these rosin-based resins, it is preferable to use fully hydrogenated rosin and hydrogenated acid-modified rosin, and it is more preferable to use fully hydrogenated rosin and hydrogenated acid-modified rosin in combination. The acrylic resin is obtained by polymerizing at least one monomer such as acrylic acid, methacrylic acid, various esters of acrylic acid, various esters of methacrylic acid, crotonic acid, itaconic acid, maleic acid, maleic anhydride, esters of maleic acid, esters of maleic anhydride, acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, vinyl chloride, and vinyl acetate. The acrylic resin is useful in that it can prevent cracks from occurring in the flux residue even in an environment with a large temperature difference and a large thermal shock. Among these acrylic resins, acrylic resins obtained by polymerizing monomers containing methacrylic acid and a monomer having an alkyl group with 2 to 6 carbon atoms, and further acrylic resins obtained by polymerizing monomers containing methacrylic acid and a monomer having an alkyl group with 2 carbon atoms are preferred. Such acrylic resins are preferred in that they suppress the stickiness of the flux residue (flux solidified product) formed and have a good crack suppression effect.

[0010] In this embodiment, the (A) component must contain (A1) a rosin resin having a softening point of 100°C or lower. This (A1) component can improve the fluidity of the flux. If the softening point of the (A1) component is higher than 100°C, the fluidity of the flux cannot be improved. From the same viewpoint, the softening point of the (A1) component is preferably 95°C or lower. There is no particular lower limit to the softening point of the (A1) component. For example, the softening point of the (A1) component may be 70°C or higher. Methods for adjusting the softening point of component (A1) include (i) adjusting the degree of polymerization of the rosin (the higher the degree of polymerization, the higher the softening point tends to be), (ii) changing the method of modifying the rosin (for example, modification with acrylic acid or maleic acid tends to increase the softening point), (iii) adjusting the molecular weight of the rosin (the higher the molecular weight, the higher the softening point tends to be), (iv) subjecting the rosin to a hydrogenation reaction, or (v) subjecting the rosin to an esterification reaction or transesterification reaction.

[0011] The blending amount of the (A1) component must be 32% by mass or more based on 100% by mass of the flux composition. If the blending amount of the (A1) component is less than 32% by mass, the generation of voids cannot be sufficiently suppressed. From the same viewpoint, the blending amount of the (A1) component is preferably 35% by mass or more relative to 100% by mass of the flux composition. On the other hand, from the viewpoint of the flux residue amount, the blending amount of the (A1) component is preferably 60% by mass or less, and more preferably 50% by mass or less.

[0012] In addition to the (A1) component, the (A) component may further contain another resin (hereinafter also referred to as the (B2) component) within the range in which the object of the present invention can be achieved. However, the blending amount of the (A1) component is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the (A) component.

[0013] The amount of the (A) component is preferably 32% by mass or more and 70% by mass or less, and more preferably 35% by mass or more and 60% by mass or less, based on 100% by mass of the flux composition. If the amount of the (A) component is more than the lower limit, the oxidation of the copper foil surface of the soldering land is prevented, making the surface more easily wetted with molten solder, so that the so-called solderability can be improved and solder balls can be sufficiently suppressed. Also, if the amount of the (A) component is less than the upper limit, the amount of flux residue can be sufficiently suppressed.

[0014] [(B) Component] The (B) activator used in this embodiment must contain (B1) a dicarboxylic acid having 3 to 5 carbon atoms. This (B1) component improves the solder cohesive strength, thereby suppressing heat dripping in the low temperature range and sufficiently suppressing the occurrence of solder balls under the components. Examples of the (B1) component include malonic acid, succinic acid, and glutaric acid. These may be used alone or in combination of two or more. It is particularly preferable to use the three acids malonic acid, succinic acid, and glutaric acid in combination.

[0015] The blending amount of the (B1) component is preferably 0.1% by mass to 12% by mass, more preferably 0.5% by mass to 10% by mass, even more preferably 1% by mass to 8% by mass, and particularly preferably 2% by mass to 6% by mass, based on 100% by mass of the flux composition. If the blending amount of the (B1) component is equal to or more than the lower limit, the effect of suppressing solder balls under the components tends to be further improved, while if the blending amount is equal to or less than the upper limit, the insulating properties of the flux composition tends to be maintained.

[0016] The (B) component may further contain (B2) a dicarboxylic acid having 12 or more carbon atoms. This (B2) component has the effect of improving the solder melting property in the high temperature range and improving the effect of suppressing solder balls under the components. Examples of the component (B2) include dodecanedioic acid, eicosanedioic acid, and dimer acid. These may be used alone or in combination of two or more.

[0017] When the (B2) component is used, its content is preferably 0.1% by mass to 8% by mass, more preferably 0.5% by mass to 5% by mass, and particularly preferably 1% by mass to 3% by mass, based on 100% by mass of the flux composition. If the (B2) component is added in an amount equal to or greater than the lower limit, the effect of suppressing solder balls tends to be further improved, whereas if the amount is equal to or less than the upper limit, the insulating properties of the flux composition tends to be maintained.

[0018] The component (B) may further contain an organic acid other than the components (B1) and (B2) (hereinafter sometimes referred to as the component (B3)). Examples of the (B3) component include monocarboxylic acids, dicarboxylic acids other than the (B1) and (B2) components, and other organic acids. These may be used alone or in combination of two or more. Monocarboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, capric acid, lauric acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, tuberculostearic acid, arachidic acid, behenic acid, lignoceric acid, and glycolic acid. Examples of dicarboxylic acids include oxalic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, tartaric acid, and diglycolic acid. Among these, adipic acid or suberic acid is preferred from the viewpoint of activity, and suberic acid is particularly preferred. Other organic acids include trimer acid, levulinic acid, lactic acid, acrylic acid, benzoic acid, salicylic acid, anisic acid, citric acid, and picolinic acid, etc. Among these, it is more preferable to use picolinic acid.

[0019] When the (B3) component is used, its amount is preferably 0.1% by mass or more and 8% by mass or less, more preferably 0.5% by mass or more and 5% by mass or less, and particularly preferably 1% by mass or more and 3% by mass or less, based on 100% by mass of the flux composition. If the amount of the (B3) component is equal to or more than the lower limit, the activation action tends to be improved, whereas if it is equal to or less than the upper limit, the insulating properties of the flux composition tend to be maintained.

[0020] In addition to the components (B1) to (B3), the component (B) may further contain another activator (hereinafter also referred to as the component (B4)) within the scope of the present invention. Examples of the component (B4) include halogen-based activators and amine-based activators. However, the total amount of the components (B1) to (B3) is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the component (B).

[0021] The blending amount of the (B) component is preferably 0.5% by mass or more and 15% by mass or less, more preferably 1% by mass or more and 12% by mass or less, and particularly preferably 1.5% by mass or more and 10% by mass or less, based on 100% by mass of the flux composition. If the blending amount of the (B) component is equal to or more than the lower limit, the activation action tends to be improved, whereas if the blending amount is equal to or less than the upper limit, the insulating property of the flux composition tends to be maintained.

[0022] [(C) component] The (C) hydroxyl-containing compound used in this embodiment must contain (C1) a hydroxyl-containing compound having a residual rate of 40 mass% or more at 240° C. in thermogravimetry. This component (C1) can improve the fluidity of the flux. Here, the conditions for the thermogravimetry are, for example, a temperature rise rate of 10° C. / min and a nitrogen atmosphere (200 mL / min). Examples of the (C1) component include isobornylcyclohexanol (residual rate at 240°C: 44% by mass) and polyoxyalkylene glycol. Examples of the polyoxyalkylene glycol include a block copolymer of polyethylene glycol-polypropylene glycol-polyethylene glycol (residual rate at 240°C: 99% by mass). These may be used alone or in combination of two or more. From the viewpoint of balance between printability and flux fluidity, it is preferable to use isobornylcyclohexanol and polyoxyalkylene glycol in combination. The mass ratio of isobornylcyclohexanol to polyoxyalkylene glycol (isobornylcyclohexanol / polyoxyalkylene glycol) is preferably 1 / 3 or more and 3 or less, more preferably 1 / 2 or more and 2 or less, and particularly preferably 1 or more and 3 / 2 or less.

[0023] The blending amount of the (C1) component must be 10% by mass or more based on 100% by mass of the flux composition. If the blending amount of the (C1) component is less than 10% by mass, the generation of voids cannot be sufficiently suppressed. From the same viewpoint, the blending amount of the (C1) component is preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and particularly preferably 30% by mass or more, based on 100% by mass of the flux composition. On the other hand, from the viewpoint of solder melting property, the blending amount of the (C1) component is preferably 50% by mass or less, and more preferably 40% by mass or less.

[0024] The blending amount of the (C) component is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 40% by mass or less, based on 100% by mass of the flux composition. When the blending amount of the (C) component is equal to or more than the lower limit, the effect of suppressing the generation of voids can be improved. When the blending amount of the (C) component is equal to or less than the upper limit, the solder melting property can be ensured.

[0025] [(D) component] From the viewpoint of printability, etc., the flux composition according to this embodiment preferably further contains (D) a thixotropic agent. Examples of the thixotropic agent used here include hardened castor oil, amides, kaolin, colloidal silica, organic bentonite, and glass frit. These may be used alone or in combination of two or more.

[0026] When component (D) is used, its content is preferably 1% by mass or more and 20% by mass or less, and more preferably 2% by mass or more and 12% by mass or less, based on 100% by mass of the flux composition. If the content is less than the lower limit, thixotropy is not obtained and sagging tends to occur easily, while if it exceeds the upper limit, the thixotropy is too high and printing defects tend to occur easily.

[0027] [solvent] From the viewpoint of printability, the flux composition according to the present embodiment preferably further contains a solvent. As the solvent used here, a known solvent can be appropriately used. As such a solvent, it is preferable to use a solvent having a boiling point of 170° C. or more. In addition, a glycol-based solvent is preferable. Examples of such solvents include diethylene glycol, dipropylene glycol, triethylene glycol, hexylene glycol, hexyl diglycol, 1,5-pentanediol, methyl carbitol, butyl carbitol, 2-ethylhexyl diglycol (EHDG), octanediol, phenyl glycol, diethylene glycol monohexyl ether, tetraethylene glycol dimethyl ether, dibutyl maleic acid, etc. These solvents may be used alone or in combination of two or more.

[0028] When a solvent is used, the amount of the solvent is preferably 10% by mass or more and 50% by mass or less with respect to 100% by mass of the flux composition. If the amount of the solvent is within the above range, the viscosity of the resulting solder composition can be appropriately adjusted to an appropriate range.

[0029] [Antioxidants] From the viewpoint of solder melting property, the flux composition according to the present embodiment preferably further contains an antioxidant. As the antioxidant used here, a known antioxidant can be appropriately used. Examples of the antioxidant include sulfur compounds, hindered phenol compounds, and phosphite compounds. Among these, hindered phenol compounds are preferred.

[0030] Examples of the hindered phenol compound include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid][ethylene bis(oxyethylene)], N,N'-bis[2-[2-(3,5-di-tert-butyl-4-hydroxyphenyl)ethylcarbonyloxy]ethyl]oxamide, and N,N'-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}hydrazine.

[0031] When an antioxidant is used, the blending amount is preferably 0.1% by mass or more and 5% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less, based on 100% by mass of the flux composition. If the blending amount of the antioxidant is equal to or more than the lower limit, the solder melting property tends to be improved, whereas if the blending amount is equal to or less than the upper limit, the insulating property of the flux composition tends to be maintained.

[0032] [Other ingredients] In addition to the (A), (B), (C), and (D) components, the solvent, and the antioxidant, other additives and even other resins can be added to the flux composition used in this embodiment as necessary. Examples of other additives include antifoaming agents, modifiers, matting agents, and foaming agents. The amount of these additives to be added is preferably 0.01% by mass or more and 5% by mass or less with respect to 100% by mass of the flux composition.

[0033] [Solder composition] Next, the solder composition according to the present embodiment will be described. The solder composition according to the present embodiment contains the flux composition according to the present embodiment described above and the solder powder (E) described below. The amount of the flux composition is preferably 5% by mass or more and 35% by mass or less, more preferably 7% by mass or more and 15% by mass or less, and particularly preferably 8% by mass or more and 12% by mass or less, relative to 100% by mass of the solder composition. When the amount of the flux composition is less than 5% by mass (when the amount of the solder powder exceeds 95% by mass), the flux composition as a binder is insufficient, so that it tends to be difficult to mix the flux composition and the solder powder. On the other hand, when the amount of the flux composition is more than 35% by mass (when the amount of the solder powder is less than 65% by mass), when the obtained solder composition is used, it tends to be difficult to form a sufficient solder joint.

[0034] The solder composition according to the present embodiment is preferably a halogen-free or non-halogen type. Even if the solder composition is compatible with halogen-free printed wiring boards, it can suppress the generation of solder balls at the same level as when a halogen-based activator is used, so it can be particularly preferably used as a halogen-free or non-halogen type solder composition. The halogen-free solder composition preferably has a chlorine concentration of 900 ppm by mass or less (more preferably, 100 ppm by mass or less, particularly preferably, 0 ppm by mass), a bromine concentration of 900 ppm by mass or less (more preferably, 100 ppm by mass or less, particularly preferably, 0 ppm by mass), an iodine concentration of 900 ppm by mass or less (more preferably, 100 ppm by mass or less, particularly preferably, 0 ppm by mass), and a halogen concentration of 1500 ppm by mass or less (more preferably, 300 ppm by mass or less, particularly preferably, 0 ppm by mass). Examples of halogen include fluorine, chlorine, bromine, and iodine. The chlorine, bromine and halogen concentrations in the solder composition can be measured according to the method described in JEITA ET-7304A, or simply calculated from the components and their amounts in the solder composition.

[0035] [(E) component] The solder powder (E) used in this embodiment is preferably made of only lead-free solder powder, but may be lead-containing solder powder. The solder alloy in this solder powder preferably contains at least one selected from the group consisting of tin (Sn), copper (Cu), zinc (Zn), silver (Ag), antimony (Sb), lead (Pb), indium (In), bismuth (Bi), nickel (Ni), cobalt (Co) and germanium (Ge). The solder alloy in the solder powder is preferably an alloy mainly composed of tin. More preferably, the solder alloy contains tin, silver, and copper. Furthermore, the solder alloy may contain at least one of antimony, bismuth, and nickel as an additive element. According to the flux composition of the present embodiment, even when a solder alloy containing an additive element that is easily oxidized, such as antimony, bismuth, and nickel, is used, the generation of voids can be suppressed. Here, lead-free solder powder refers to a powder of solder metal or alloy to which no lead is added. However, the presence of lead as an unavoidable impurity in the lead-free solder powder is permitted, but in this case, the amount of lead is preferably 300 ppm by mass or less.

[0036] Specific examples of alloys of lead-free solder powder include Sn-Ag-Cu, Sn-Cu, Sn-Ag, Sn-Bi, Sn-Ag-Bi, Sn-Ag-Sb-Bi, Sn-Ag-Cu-Bi, Sn-Ag-Cu-Ni, Sn-Ag-Cu-Bi-Sb, Sn-Ag-Bi-In, Sn-Ag-Cu-Bi-In-Sb, and Sn-Sb. Among these, from the viewpoint of the strength of the solder joint, Sn-Ag-Cu or Sn-Sb solder alloys are preferably used. The melting point of Sn-Ag-Cu solder is usually 200°C or higher and 250°C or lower. Incidentally, among Sn-Ag-Cu based solders, the melting point of solders with a low silver content is 210° C. or higher and 250° C. or lower (more preferably, 220° C. or higher and 240° C. or lower). As the Sn-Sb based solder alloy, a Sb-5.0Sb solder alloy is particularly used.

[0037] The average particle size of component (E) is usually 1 μm or more and 40 μm or less, but from the viewpoint of compatibility with electronic boards having narrow pitches of solder pads, it is more preferably 1 μm or more and 35 μm or less, even more preferably 2 μm or more and 35 μm or less, and particularly preferably 3 μm or more and 32 μm or less. The average particle size can be measured by a dynamic light scattering type particle size measuring device.

[0038] [Method of manufacturing solder composition] The solder composition of this embodiment can be produced by blending the above-described flux composition and the above-described (E) solder powder in the above-described predetermined ratio, and stirring and mixing them.

[0039] [Electronic board] Next, the electronic board according to the present embodiment will be described. The electronic board according to the present embodiment is characterized by having a soldered portion using the solder composition according to the present embodiment. The electronic board according to the present embodiment can be manufactured by mounting electronic components on an electronic board (such as a printed wiring board) using the solder composition. Examples of the coating device used here include a screen printer, a metal mask printer, a dispenser, and a jet dispenser. In addition, electronic components can be mounted on an electronic board by a reflow process in which electronic components are placed on the solder composition applied by an application device and heated under specified conditions in a reflow furnace to mount the electronic components on a printed wiring board.

[0040] In the reflow process, an electronic component is placed on the solder composition and heated in a reflow furnace under predetermined conditions. This reflow process allows a sufficient solder joint to be formed between the electronic component and the printed wiring board. As a result, the electronic component can be mounted on the printed wiring board. The reflow conditions may be appropriately set according to the melting point of the solder. For example, when using a Sn-Ag-Cu solder alloy, the preheat temperature is preferably 150°C or higher and 200°C or lower. The preheat time is preferably 60 seconds or higher and 120 seconds or lower. The peak temperature is preferably 230°C or higher and 270°C or lower. The holding time at a temperature of 220°C or higher is preferably 30 seconds or higher and 120 seconds or lower.

[0041] Furthermore, the flux composition, the solder composition, and the electronic board according to the present embodiment are not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. For example, in the electronic substrate, the printed wiring board and the electronic component are bonded by a reflow process, but the present invention is not limited thereto. For example, instead of the reflow process, the printed wiring board and the electronic component may be bonded by a process (laser heating process) of heating the solder composition using laser light. In this case, the laser light source is not particularly limited and can be appropriately adopted according to the wavelength that matches the absorption band of the metal. Examples of the laser light source include solid lasers (ruby, glass, YAG, etc.), semiconductor lasers (GaAs, InGaAsP, etc.), liquid lasers (dye, etc.), and gas lasers (He-Ne, Ar, CO2, excimer, etc.). EXAMPLES

[0042] The present invention will now be described in more detail with reference to examples and comparative examples, but the present invention is not limited to these examples. The materials used in the examples and comparative examples are shown below. (Component (A1)) Rosin-based resin A: Special modified rosin (softening point 85°C to 95°C), product name "Haritac FG-90", manufactured by Harima Chemicals Co., Ltd. Rosin-based resin B: Formylated rosin (softening point 79°C to 88°C), trade name "FORAL-AX", manufactured by Eastman Chemical Company ((A2) component) Rosin-based resin C: Acrylic acid modified hydrogenated rosin (softening point 124°C to 134°C), product name "Pine Crystal KE-604", manufactured by Arakawa Chemical Industries Co., Ltd. ((B1) component) Dicarboxylic acid A: Malonic acid Dicarboxylic acid B: Succinic acid Dicarboxylic acid C: Glutaric acid ((B2) component) Dicarboxylic acid D: Dodecanedioic acid Dicarboxylic acid E: Dimer acid (Component (B3)) Organic acid A: Adipic acid Organic acid B: Sebacic acid ((C1) component) Hydroxyl-containing compound A: isobornylcyclohexanol (residual rate at 240°C in thermogravimetry is 44% by mass), product name "MTPH", manufactured by Nippon Terpene Chemical Co., Ltd. Hydroxyl-containing compound B: Polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer (residual rate at 240°C in thermogravimetry is 99% by mass) ((D) component) Thixotropic agent: Trade name "Himako", manufactured by KF Trading Co., Ltd. (Other ingredients) Solvent: Hexyl diglycol, manufactured by Nippon Nyukazai Co., Ltd. ((E) component) Solder powder: alloy composition is Sn-5.0Sb, particle size distribution is 5-20μm, solder melting point is 238-241℃

[0043] [Example 1] 24 mass% of rosin-based resin A, 12 mass% of rosin-based resin B, 19 mass% of hydroxyl-containing compound A, 15 mass% of hydroxyl-containing compound B, 0.6 mass% of dicarboxylic acid A, 0.3 mass% of dicarboxylic acid B, 3 mass% of dicarboxylic acid C, 0.5 mass% of dicarboxylic acid D, 16.6 mass% of solvent, and 9 mass% of thixotropic agent were charged into a container and mixed using a planetary mixer to obtain a flux composition. Thereafter, 12% by mass of the obtained flux composition and 88% by mass of the solder powder (total of 100% by mass) were placed in a container and mixed with a planetary mixer to prepare a solder composition.

[0044] [Examples 2 to 9] A solder composition was obtained in the same manner as in Example 1, except that the materials were mixed according to the composition shown in Table 1. [Comparative Examples 1 to 8] A solder composition was obtained in the same manner as in Example 1, except that the materials were mixed according to the composition shown in Table 1.

[0045] <Evaluation of solder composition> The solder composition was evaluated (voids, balls under the chip) by the following method. The results are shown in Table 1. (1) Void The solder composition was printed on the substrate using a metal mask with a mask thickness of 80 μm and a mask aperture ratio of 80%. Next, a 0.5 mm PLGA (plastic land grid array package, number of pads: 228, surface treatment: NiAu) was mounted, and a reflow process was performed under the following heating conditions to prepare a substrate for evaluation. (Heating conditions) Reflow equipment: Tamura Manufacturing's "TNP25-538EM", O2 concentration 50ppm or less Preheat temperature: 140-200℃ for 80 seconds Holding time above 238℃: 45 seconds Peak temperature: 260℃ Then, using an X-ray inspection device, Nordson's "Dage XD7600 Diamond," the solder joints of the 0.5 mm PLGA were observed, and the total void area ratio in the pads [(total void area / total pad area) x 100] was calculated. The voids were evaluated according to the following criteria. ⊚: The total void area ratio is less than 10%. ◯: The total void area ratio is 10% or more and less than 15%. △: The total void area ratio is 15% or more and less than 20%. ×: The total void area ratio is 20% or more. (2) Ball under the chip The evaluation substrate was prepared in the same manner as in (1) Evaluation of voids. Then, using an X-ray inspection device, Nordson's Dage XD7600 Diamond, we observed under the 0.5 mm PLGA chip, counted the number of solder balls that had occurred under the chip, and evaluated the balls under the chip according to the following criteria. ⊚: The number of solder balls generated is 80 or less. ◯: The number of solder balls generated is 81 or more and 120 or less. △: The number of solder balls generated is 121 or more and 160 or less. ×: The number of solder balls generated is 161 or more.

[0046] [Table 1]

[0047] As is clear from the results shown in Table 1, it was confirmed that the solder compositions of the present invention (Examples 1 to 9) were good in all respects regarding voids and balls under the chip. Note that the solder compositions of Examples 1 to 9 do not contain a halogen-based activator, and are therefore non-halogen type solder compositions. Therefore, it was confirmed that the solder composition of the present invention can sufficiently suppress the occurrence of voids and also sufficiently suppress the occurrence of solder balls under components. [Industrial Applicability]

[0048] The flux composition and solder composition of the present invention can be suitably used as a technique for mounting electronic components on electronic substrates such as printed wiring boards of electronic devices.

Claims

1. A flux composition comprising (A) a resin, (B) an activator, and (C) a hydroxyl-containing compound having a hydroxyl group, The component (A) contains (A1) a rosin-based resin having a softening point of 100° C. or lower, The component (B) contains (B1) a dicarboxylic acid having 3 to 5 carbon atoms, The component (C) contains (C1) a hydroxyl group-containing compound having a residual rate of 40% by mass or more at 240°C in thermogravimetry, The component (C1) is at least one selected from the group consisting of isobornylcyclohexanol and polyoxyalkylene glycol, The blending amount of the (A1) component is 32% by mass or more with respect to 100% by mass of the flux composition, The blending amount of the (C1) component is 20 mass% or more with respect to 100 mass% of the flux composition. Flux composition.

2. The flux composition according to claim 1, The blending amount of the (A1) component is 80% by mass or more with respect to 100% by mass of the (A) component. Flux composition.

3. The flux composition according to claim 1 or 2, Further, (D) contains a thixotropic agent, Flux composition.

4. A flux composition according to claim 1 or 2, and (E) a solder powder. Solder composition.

5. A soldered portion comprising the solder composition according to claim 4. Electronic board.

Citation Information

Patent Citations

  • Preparation of entangled cocoon filament

    JP1983087330A

  • Solder paste composition and reflow soldering method

    JP2002336993A

  • Flux and solder material and method of making the same

    JP2011173167A

  • Flux for soldering and printed wiring board using the same

    JP2014117745A

  • Solder composition and printed wiring board using the same

    JP2015142936A